The relationships among strategic performance measurement systems, IS strategic alignment, and IT infrastructure for knowledge management - Jong-min Choe (Global Business & Finance Review (GBFR), 2016)
Investigating how to develop information technology (IT) infrastructure that can effectively facilitate knowledge management (KM) activities has been an important research area. To contribute to the theoretical and practical developments in this research area, this study empirically examined the causal relationships among the use of strategic performance measurement systems (SPMS), organizational learning, information systems (IS) strategic alignment, IT infrastructure for KM, competitive applications of knowledge resources, and organizational performance. Through structured questionnaires, empirical data were collected from 117 Korean manufacturing firms that are listed on the Korean stock market. To analyze the empirical data, regression analyses were employed. The results of this study showed that SPMS significantly and positively influences organizational learning and IS strategic alignment. The strategic communications and dialogues between members of an organization, which are provided by SPMS, may enhance the degrees of IS strategic alignment. According to the results, it was found that both organizational learning and IS strategic alignment have significant and positive effects on the adoption of IT infrastructure for KM. Thus, the clear directions of IT development, which are formed through IS strategic alignment, seem to shape the goal orientations of members in a firm, and the organizational learning that is built with SPMS seems to enhance members' collaborations in the construction of IT infrastructure. This study also showed that when the degrees of IS strategic alignment are high, the effects of IT infrastructure on the competitive applications of knowledge resources are partially greater than under the low levels of IS strategic alignment. Finally, it was observed that the competitive usage of knowledge asset has a positive impact on the performance of an organization.
Keywords: 650; Strategic performance measurement systems; Organizational learning; IS strategic alignment; IT infrastructure for knowledge management; Competitive applications of knowledge resources